South of Nowhere - Deaver, Jeffery (New York : G. P. Putnam's Sons, 2025)
"A small town in Northern California is at risk of being destroyed by a failing levee, and Colter Shaw has been hired to locate a family swept away by the raging water, with mere hours to survive. But is the levee at risk of failing from natural causes or is someone sabotaging it? With the help of his sister, Dorion, the duo must save the citizens before the old town washes out at the hands of a secret conspirer"--
Keywords: Shaw, Colter -- (Fictitious character) -- Fiction; Missing persons -- Fiction; Mystery fiction; Adventure fiction; Thrillers (Fiction); Suspense fiction; Novels